Educação permanente sobre álcool e outras drogas: saberes e práticas de profissionais de um curso de segurança pública (Brazilian Journal of Health Research, 2019)
Permanent education about the use of alcohol and other drugs: knowledge and practices of professionals enrolled in a public security course